Taxonomic circumscription, new synonym and lectotypification of Saxifraga umbellulata (Saxifragaceae) - Midday, Mrinmoy; Ghosh, Jayanta; Maity, Debabrata (Phytotaxa, 2021)
Saxifraga umbellulata Hook & Thomson (1857:71), an Eastern Himalayan member of the genus Saxifraga Linnaeus (1753:398) (Saxifragaceae) was described based on specimens collected from the Sikkim Himalaya. The species was characterized by having a brown, densely glandular stem; many basal, very thick, fleshy (leathery), glabrous or sparsely setose-ciliate leaves, forming a rosette; few to several, erect, yellow flowers in a terminal subumbellate inflorescence. At present, the species is distributed in Nepal, India (Sikkim), Bhutan and China (Tibet) (Pan et al. 2001, Maity et al. 2018). Later Marquand and Airy Shaw described S. umbellulata f. pectinata Marquand & Airy Shaw in Marquand (1929:183) (Fig. 1) based on a few specimens, collected by F. Kingdon Ward from Pasum Lake in Tibet (Xizang), China, with cartilaginous setose-ciliate margin of basal leaves and yellow flowers. Pan (1992) raised this taxon to the rank of variety as S. umbellulata var. pectinata (C.Marquand & Airy Shaw) Pan (1992:165). Until now the variety has been accepted taxonomically.